Introduction to Apparel Production Workbook - Apple, Laurie M. (Open textbook library., 2023)
Welcome to Introduction to Apparel Production. Whether you are part of the college class or learning on your own, you will gain important concepts and techniques in beginning apparel production. This workbook is to accompany the activities through in person teaching or online learning. There will be graphics and videos to help guide you through each step of this workbook. There are 6 learning units and a sewing projects unit in this workbook. The sewing projects unit contains 4 projects: tote bag, skirt, shirt and pants. The pattern numbers may change due to the availability of patterns.